Perancangan Framework ITIL untuk Meningkatkan Tata Kelola Teknologi Informasi pada LMS - Indra Dharma Wijaya, S.T, M.T; Nurhidayah; Hanum Mufida Akhsanti; Yunika Puteri Dwi Antika (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2024)
This research describes the analysis of Information Technology (IT) service management on the Learning Management System (LMS) of the Information Technology Department at Politeknik Negeri Malang using the Information Technology Infrastructure Library (ITIL) V3 framework, especially in the Service Operation domain. ITIL V3 is a best practice concept in IT service management that is non-proprietary and non-prescriptive. The focus of the research is on the main processes of IT Service Management (ITSM), namely service support and service delivery. The research method uses a qualitative approach with interviews to related parties and observation by distributing questionnaires to students. The results identified several problems in the ITSM process, especially in Incident Management, Problem Management, and Request Fulfillment. The conclusion shows that although the LMS service is good enough, improvements are still needed in event management, incident recovery, and problem handling in order to optimize IT services. Recommendations were developed based on the findings of the problem, including the design of an ITIL infrastructure involving the development of existing processes. It is expected that these recommendations can improve the effectiveness and efficiency of IT services, address challenges in LMS operations, and produce better service quality. Keywords– Information Technology, LMS, ITIL, service operation, ITSM